The Application of Prebiotics in Poultry Production - Hajati, H.; Rezaei, M. (International Journal of Poultry Science, 2010)
For several decades, antibiotics and chemotherapeutics in prophylactic doses have been used in poultry diet to improve their welfare and to obtain economic benefits in terms of improved animal performance and reduced medication costs. With increasing concerns about antibiotic resistance, there is increasing interest in finding alternatives to antibiotics for poultry production. Prebiotics are one of the alternatives that can improve poultry performance through altering gut microflora. Furthermore, high protein prices and environmental concerns have pressured the industry to search for methods for reducing dietary protein levels.